Torus Palatinus - Separa, Dennis G. (The Journal of the Philippine Dental Association)
Torus palatinus or palatal torus, is a benign but slowly growing, bony overgrowth of the palatine processes of the maxillae and sometimes the horizontal plates of the palatine bones. It occurs bilaterally along the median suture on the oral surface of the hard palate. In this report, we will present a case of a 52-year-old woman who sought treatment in the dental infirmary of the College of Dentistry of the University of the East.